The Influence Of Promotion, Prices And School Image On The Acceptance Of New Students At SDS Kristen Tabqha, Batam City: - Sinaga , Anjes Mara; Nuraeni , Brigida Endah; Atmojo , Agus Sekti Susila (Tractare: Jurnal Ekonomi-Manajemen, 2024)
This research aims to determine the influence of promotion, price and school image, both partially and simultaneously, on the acceptance of new students at SDS Kristen Tabqha, Batam City. This research used a quantitative method with a population of 369 parents using the Slovin method to produce a sample of 100 parents and data collection using a questionnaire. The results of this research found that the promotion variable had a tcount of 3.578 > ttable 1.661 with a significance level of 0.001 < 0.05, so promotion had a positive and significant effect on the acceptance of new students at SDS Kristen Tabqha, Batam City. The price variable has a tcount of 2.340 > ttable 1.661 with a significance level of 0.021 < 0.05, so price has a positive and significant effect on the acceptance of new students at SDS Kristen Tabqha, Batam City. The school image variable has tcount 8.308 > ttable 1.661 with a significance level of 0.000 < 0.05, so school image has a positive and significant effect on the acceptance of new students at SDS Kristen Tabqha, Batam City. From the F test it is known that the fcount for promotion, price and school image is 91.196 > ftable 2.70 with a significance level of 0.000 < 0.05. This shows that the promotion, price and school image variables simultaneously have a positive and significant effect on the acceptance of new students at SDS Kristen Tabqha, Batam City.